Implementation of Heart Management in Creating a Religious Learning Environment at Daarut Tauhid Elementary School, Bandung - Asrivi, Queen Elvina Sevtivia; Faizin, Faizin (Prodi PGMI STIT Sunan Giri Bima, 2025)
This study aims to explore the implementation of the Manajemen Qolbu (MQ) concept in shaping a religious learning environment at SD Daarut Tauhiid Bandung. MQ is a spiritual-based educational approach that emphasizes the management of the heart (qalbu) as the center of moral, ethical, and spiritual awareness. Using a descriptive qualitative method, data were collected through observations, in-depth interviews, and documentation. The findings reveal that MQ is systematically integrated into daily school activities, including morning and evening dzikr, collective prayers, spiritual mentoring, and the modeling of good character by teachers. The unique Daarut Tauhiid curriculum, based on seven core pillars tauhid, manners (adab), exemplary behavior, independence, spiritual habits, integration of religious and secular knowledge, and social care supports the creation of a harmonious, inclusive, and spiritually rich learning atmosphere. MQ contributes significantly to improving student discipline, empathy, self-awareness, emotional regulation, and intrinsic motivation. Despite facing challenges such as limited time and varying levels of understanding among educators and students, the structured implementation of MQ proves to be an effective character education strategy. This research highlights MQ as a holistic and contextual solution for integrating spiritual values into formal education and offers a replicable model for other primary schools seeking to nurture students with strong religious and moral foundations. Abstrak : Penelitian ini bertujuan untuk mengkaji penerapan konsep Manajemen Qolbu (MQ) dalam membentuk lingkungan belajar yang religius di SD Daarut Tauhiid Bandung. MQ merupakan pendekatan spiritual yang berfokus pada pengelolaan hati (qalbu) sebagai pusat kesadaran moral dan akhlak. Melalui Metode kualitatif deskriptif, data dikumpulkan melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa MQ terintegrasi dalam berbagai aspek pembelajaran dan budaya sekolah, seperti pembiasaan dzikir, doa harian, mentoring ruhiyah, serta keteladanan guru. Kurikulum khas Daarut Tauhiid yang berbasis pada tujuh pilar utama tauhid, adab, keteladanan, kemandirian, dzikir, integrasi ilmu, dan kepedulian sosial mendukung terwujudnya lingkungan belajar yang spiritual, harmonis, dan kondusif. Penerapan MQ terbukti meningkatkan kedisiplinan, empati, ketenangan batin, dan motivasi belajar siswa. Namun, implementasi MQ juga menghadapi tantangan, seperti keterbatasan waktu dan resistensi awal dari sebagian guru atau siswa. Penelitian ini merekomendasikan pembinaan guru yang berkelanjutan dan integrasi formal MQ dalam kebijakan sekolah untuk keberlanjutan program. MQ terbukti menjadi strategi efektif dalam pembentukan karakter religius dan lingkungan belajar yang rahmatan lil 'alamin.